Adoption of Disciplinary Strategies in Classroom by the Secondary Level Teachers in Kathmandu - Panday, Nikesh (Kalika Journal of Multidisciplinary Studies, 2024)
Favorable behavior modification is the goal of school discipline to foster a supportive learning environment. Students’ academic performance improves when discipline is established in secondary schools. Discipline-related problems can have a long-lasting impact on a student’s academic achievement and personal growth during the crucial secondary school years. Secondary-level teachers sometimes encounter circumstances where they must deal with disrespect, hostility, and numerous verbal and physical abuses in the classroom. Additionally, they are under pressure from unattainable expectations and are blamed for systemic failures that affect many children, which makes it even harder for them to survive in challenging classrooms. Therefore, this small-scale exploratory and descriptive qualitative research examines secondary-level teachers’ opinions and experiences about challenging classroom settings. The researcher conducted a semi-structured interview with the secondary-level teachers. The study findings can be divided into three themes : Discipline-based Strategy Definition, Classroom Behavior Issues among the students, and Efficacy of teachers’ disciplinary techniques. This study reveals that teachers apply different disciplinary strategies to handle classroom behavioral problems. Because teachers are not entirely to blame for the problematic circumstances, the study’s findings suggested that when teachers struggle to keep the classroom in order, they should expand their roles as change agents by inspiring students, changing the way instruction is delivered, creating effective plans and classroom strategies, and increasing awareness among stakeholders. There is no pre-made answer or definitive outcome for this issue, as the overall concept of classrooms and their layout has been continually revised worldwide.